2021
DOI: 10.3390/su13169467
|View full text |Cite
|
Sign up to set email alerts
|

Self-Directedness for Sustainable Learning in University Studies: Lithuanian Students’ Perspective

Abstract: The paper analyzes Lithuanian students’ preparedness for sustainable learning from the perspective of self-directedness. The data for the study were collected using a questionnaire that explored students’ perceptions in line with ten indicators of self-directed learning. The research sample (n = 309) was composed of the third and fourth year undergraduates accomplishing their degrees in various areas of studies. The data analysis revealed how students perceive their readiness for sustainable learning. Goal set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
3
6
0
Order By: Relevance
“…Also, another assumption can be made that despite the fact that adult learners' ESP classes are organized online, which is less timeconsuming, they might still cope with some difficulties to manage their time and stress while balancing between family, work and other commitments they have. These study results are compatible with the findings of Burkšaitienė et al (2021) which suggest that inabilities to deal with time and procrastination management that resulted in poor stress management might have been caused by the COVID-19 pandemic and a sudden switch to online learning. Thus, helping students avoid anxiety and manage their stress levels might develop their self-directedness.…”
Section: Resultssupporting
confidence: 91%
“…Also, another assumption can be made that despite the fact that adult learners' ESP classes are organized online, which is less timeconsuming, they might still cope with some difficulties to manage their time and stress while balancing between family, work and other commitments they have. These study results are compatible with the findings of Burkšaitienė et al (2021) which suggest that inabilities to deal with time and procrastination management that resulted in poor stress management might have been caused by the COVID-19 pandemic and a sudden switch to online learning. Thus, helping students avoid anxiety and manage their stress levels might develop their self-directedness.…”
Section: Resultssupporting
confidence: 91%
“…Moreover, in connection with our hypothesis testing, we have shown that students have a similarly good basement for their personal development. Our research results can be supported by Gay [56] and Yusupova et al [57]; in addition to the importance of the contribution of studies to professional development, personal development is equally emphasized [58]. Derényi [30] similarly agrees that with the internationalization of higher education, students can learn the competencies they need for their studies and their future work.…”
Section: Discussionsupporting
confidence: 77%
“…To estimate the student's knowledge of the subject domain, a model based on the Q-learning approach is used, but other models such as Bayesian Knowledge Tracing can be added easily using the interface for strategy plug-ins. This allows using our approach in guided learning [46,47] and export these data for reviewing by teachers and tutors and to foster integration with Learning Management Systems and Intelligent Textbooks [48] using common domain models.…”
Section: Discussionmentioning
confidence: 99%